(untitled) (Orfeu, 2023)
The purpose of this paper was to analyze themes for the prevention of musculoskeletal injuries in music students that can be included in the political-pedagogical project of the secondary-level technical professional music education in the public network of the Federal District. To this end, its approach included methodological procedures of documentary and literature. Semi-structured interviews were conducted as a methodological procedure for data generation. The content analysis proposed by Bardin (2016) was used to analyze the generated data. Based on the content analysis, three central categories emerged from the narratives of the interviewed teachers: the first was related to musculoskeletal symptoms in music students; the second was related to musculoskeletal injury risk factors in music students; the third was related to preventive behaviors for music students. After the content analysis, the position was taken that musculoskeletal injuries in music students are related to musculoskeletal overload, inadequate postures, as well as the absence of strategies for prevention practices in the school environment. The conclusion is that the inclusion of these themes in the political-pedagogical project of the Escola de Música de Brasília may contribute to the integral training and quality of life of the student. Additionally, it may help in the development of future teaching and learning strategies and more effective educational practices.